“WHEN THE HORN THAWED, THE TUNE POURED OUT”: PAVEL LUNGIN ON THE MAKING OF TAXI BLUES / «КОГДА РОЖОК ОТТАЯЛ, ПОЛИЛИСЬ ЗВУКИ МУЗЫКИ…»: ПАВЕЛ ЛУНГИН О СОЗДАНИИ ФИЛЬМА «ТАКСИ-БЛЮЗ» - Lungin Pavel S. / Лунгин П.С.; Trusevich Elizaveta S. / Трусевич Е.С.; Klemeshev Pyotr A. / Клемешев П.А. (Наука телевидения)
Russian film director Pavel Lungin explores the topic of independent cinema during perestroika, using the example of his debut film Taxi Blues, which received one of the first international awards in post-Soviet Russia—the Best Director Prize and the Special Mention of the Ecumenical Jury at the 1990 Cannes Film Festival. In the interview, the interlocutors discuss the directorial and dramaturgical tools: how symbolism is interpreted in a historical context, how the audiovisual image is constructed, what are the signs of a chronotope — and explore the image of a man at the crash of an era. For instance, in Taxi Blues, Pavel Lungin intentionally contraposes the two male characters—that of Pyort Mamonov (the image of the 90s), and of Pyotr Zaichenko (the image of a Soviet man)—clashing them against each other not only plotwise (through a dramatic conflict), but also aesthetically (through fundamentally different physiognomy and acting plastics). The director analyzes the specifics of auteur and genre filmmaking, dividing his artistic biography into a “script-writing” period, when his films were highly successful in Soviet distribution, and a “directing” period, when he, being in the new historical conditions, began to make independent auteur films. Another question raised is why a full-fledged “New Wave” has not emerged in Russia, similar to those that had formed in French and English cinema. Lungin recalls and evaluates the forgotten figure of Marin Karmitz, who not only produced the New Wave directors, but also had an auteur cinema distribution network—an interesting experience of distribution in Europe, which can be actualized in scientific research to answer a very timely question: can auteur films be successful at the box office? Thus, the interview covers not only the early period of Pavel Lungin’s work (given that at the time of Taxi Blues there was no Internet yet, and many reviews and analytical articles about the film are still not digitized). Most importantly, the film Taxi Blues fits into the historical context; and this fact creates a cultural field both for modern interpretations and for understanding the art of perestroika—information about which is still insufficient, resulting in the absence of full-fledged analytical comprehension. In the interview, we also trace parallels with the processes that were taking place in world cinema—the New Wave in French cinema, the British “angry young men”, and the “Youth Rebellion” in Hollywood. Российский режиссер Павел Лунгин раскрывает тему «независимого кино» в период перестройки на примере производства своего дебютного фильма «Такси-блюз», получившего одну из первых международных наград в постсоветской России — приз за лучшую режиссерскую работу и специальное упоминание экуменического жюри на Каннском фестивале 1990 года. Анализируются режиссерские и драматургические инструментарии картины: трактовка системы символов в историческом контексте, построение звукозрительного образа, приметы хронотопа. Исследуется образ человека на сломе эпох: в фильме «Такси-блюз» Павел Лунгин преднамеренно противопоставил два мужских образа: в исполнении Петра Мамонова (образ 90-х) и Петра Зайченко (образ советского человека), столкнув их не только фабульно (посредством драматургического конфликта), но и эстетически (принципиально различная физиогномика и актерская пластика). Режиссер также анализирует специфику авторского и жанрового кинематографа, разделяя свою творческую биографию на «сценарный» период, когда его фильмы были очень успешны в советском прокате, и «режиссерский», когда он начал снимать независимое авторское кино уже в новых исторических условиях. Поднимается и вопрос о том, почему в России не возникла полноценная «новая волна», подобно тем, что сформировались во французском и английском кино. Павел Лунгин вспоминает и дает оценку забытой фигуре продюсера Марина Кармица, не только продюсировавшего режиссеров «новой волны», но и имевшего сеть кинопроката авторского кинематографа — интересный опыт европейской дистрибуции, который можно актуализировать в научных исследованиях, чтобы ответить на очень своевременный вопрос: может ли авторское кино быть успешным в прокате? Таким образом, в интервью исследуется не только ранний период творчества Павла Лунгина (с учетом того, что во времена «Такси-блюз» еще не было Интернета, и многие рецензии и аналитические статьи о фильме до сих пор не оцифрованы). Самое главное — фильм «Такси-блюз» вписывается в исторический контекст, что создает культурологическое поле как для современных трактовок, так и для понимания искусства перестройки, информации о котором до сих пор недостаточно, вследствие чего отсутствует и полноценное аналитическое осмысление. Также в интервью проводятся различные аналогии с процессами, происходившими в мировом кино: даются характеристики «новой волне» французского кино, «поколению рассерженных» в Великобритании, «поколению молодежного бунта» в Голливуде.